Dynamics of separate indicators of blood circulation of weightlifters at different training stages - Talibov, A. Kh.; Kuvanov, V. A.; Kuvanov, Ya. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to identify changes in athletes` cardiovascular system parameters under the influence of physical loads and identify the peculiarities of the state of adaptation mechanisms.